Selective hydrolysis of α-oxo ketene N,S-acetals in water: switchable aqueous synthesis of β-keto thioesters and β-keto amides - Yu, Haifeng; Zhang, Wanting; Cui, Xuejing; Liu, Zida; Zhang, Xifu; Zhao, Xiaobo (Beilstein Journal of Organic Chemistry, 2024)
An eco-friendly selective hydrolysis of chain α-oxo ketene N,S-acetals in water for the switchable synthesis of β-keto thioesters and β-keto amides is reported. In refluxing water, the hydrolysis reactions of α-oxo ketene N,S-acetals in the presence of 1.0 equiv of dodecylbenzenesulfonic acid effectively afforded β-keto thioesters in excellent yield, while β-keto amides were successfully obtained in excellent yield when the hydrolysis reactions were carried out in the presence of 3.0 equiv of NaOH. The green approach to β-keto thioesters and β-keto amides avoids the use of harmful organic solvents, thiols and thiolacetates as well as amines, which could result in serious environmental and safety issues.
Keywords: α-oxo ketene N,S-acetals; β-keto amide; β-keto thioester; dodecylbenzenesulfonic acid; hydrolysis